Establishing Crime Prevention Through Environmental Design Model - MD Sakip, Siti Rasidah; Megat Abdul Rahim, Puteri Rohani; Mat Nayan, Nadiyanti (International Journal of Sustainable Construction Engineering and Technology, 2023)
Rapid urbanization in Malaysia has led to an increasing crime rate, necessitating an understanding of the relationships between crime, the environment, and community. This study examines the causal connections among fear of crime, sense of community, and Crime Prevention Through Environmental Design (CPTED) using a quantitative approach with 171 respondents in Selangor and Putrajaya. Previous research has highlighted the psychological effects of crime and the efficacy of defensible space and CPTED in reducing crime in residential areas. However, the causal relationship between sense of community and CPTED requires further investigation. The study's causal model confirms that fear of crime does significantly influence CPTED implementation and the sense of community. Additionally, a strong sense of community significantly impacts CPTED, underscoring the role of community engagement in enhancing crime prevention strategies. These findings have practical implications for policymakers and urban planners, emphasizing the importance of addressing fear of crime to create safer environments that foster community cohesion. Strategies may include improved lighting, surveillance systems, and community-building initiatives. Further research can explore underlying mechanisms and moderating factors. Ultimately, addressing fear of crime, sense of community, and implementing CPTED can enhance community well-being and promote a sense of security.